2013
DOI: 10.1128/jvi.00304-13
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi Protein ACBD3, an Interactor for Poliovirus Protein 3A, Modulates Poliovirus Replication

Abstract: eWe have shown that the circulating vaccine-derived polioviruses responsible for poliomyelitis outbreaks in Madagascar have recombinant genomes composed of sequences encoding capsid proteins derived from poliovaccine Sabin, mostly type 2 (PVS2), and sequences encoding nonstructural proteins derived from other human enteroviruses. Interestingly, almost all of these recombinant genomes encode a nonstructural 3A protein related to that of field coxsackievirus A17 (CV-A17) strains. Here, we investigated the reperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…To investigate the importance of GBF1 activity for PI4KIII␤ recruitment, we utilized an in vitro system with HeLa S10 cell extracts (21). RNA coding for CVB3 3A was translated in these cell extracts in the absence or presence of brefeldin A (BFA), a well-known inhibitor of GBF1 (34). Subsequently, the membranes were isolated by centrifugation and the membrane-associated proteins were analyzed by Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the importance of GBF1 activity for PI4KIII␤ recruitment, we utilized an in vitro system with HeLa S10 cell extracts (21). RNA coding for CVB3 3A was translated in these cell extracts in the absence or presence of brefeldin A (BFA), a well-known inhibitor of GBF1 (34). Subsequently, the membranes were isolated by centrifugation and the membrane-associated proteins were analyzed by Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…CVB3 3A and PV 3A both interact with the N terminus of GBF1 (7,8) as well as ACBD3 (9). However, we and others recently showed that the PI4KIII␤ recruitment by 3A of PV and CVB3 seems to occur independently of both GBF1/Arf1 and ACBD3 (9,10). We studied this by individually expressing mutant 3A proteins of CVB3 that no longer interact with GBF1 (9).…”
mentioning
confidence: 99%
“…This pathway transiently protects cells against PV-induced cell death and may provide the virus with sufficient time to replicate. We previously showed that the non-structural 3A protein of PV interacts with CREB3 (Teoule et al, 2013). However, the role of the 3A protein in this process remains to be investigated.…”
Section: Herpmentioning
confidence: 99%
“…Herp is under the transcriptional control of cAMP response element-binding protein 3 (CREB3), a member of the ER membrane-bound CREB/ATF (activating transcription factor) family of proteins, which is rapidly activated in response to cellular stress signals via the Golgi regulated intramembrane proteolysis (RIP) pathway (Asada et al, 2011;Chan et al, 2011;Raggo et al, 2002). We had also identified CREB as interacting with the PV nonstructural protein 3A (Teoule et al, 2013), a multifunction protein involved in PV replication, both directly and indirectly, via massive remodeling of host intracellular membranes (Belov & van Kuppeveld, 2012;Paul & Wimmer, 2015;van Kuppeveld et al, 2010). We therefore hypothesized that PVinduced Ca 2+ release from the ER and apoptosis might be modulated by the CREB3/Herp signalling pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation